Peningkatan Prestasi Belajar Matematika Menggunakan Model Cycle-5e Berbantu Modul Statistika - Riani Widiastuti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2021)
This study aims to describe effectiveness use of Model Cycle-5E assisted modul Statistika to increase the student’s achievement in subject class XII SMAN 4 Yogyakarta. The classroom action research steps in cycle I are: arrange the planning to have development, conduct the planning, observe the effect of the action, and reflect on the things that have been done. If the results obtained in one cycle is not in accordance with targeted, it will repeat again in the next cycle, and so on, up to cycles III. The results of this research after the use of Model Cycle-5E modul Statistika assisted proved to be effective: 1) The learning achievement class XII SMAN 4 Yogyakarta is increase. Seen from the increasing in mastery learning students each cycle of: 13 students in cycle I, 27 students in cycle II, 29 students at the third cycle. There is an increasing in the percentage of completeness each cycle, 40.63% in cycle I, 84,38% in cycle II, and 100% in cycle III. Learning achievement of at least a 80% of students achieving mastery minimal completeness criteria 75. 2) The using of Model Cycle-5E assisted modul Statistika good because of the positive response from students. This can be seen from the interviewing and learning Model Cycle-5E shows most of the students give positive responses and few students give negative feedback.